Designing Student’s Worksheet on Statistical Topics using Lesson Study Approach in Collaboration with MGMP Matematika SMA Pesisir Selatan - Syafriandi Syafriandi; Nonong Amalita; Dina Fitria (Pelita Eksakta, 2020)
Writing students worksheet is a routine task for each teacher. In this workshop, teachers design the worksheet using lesson study approach. Before design the learning material which is lesson plan and student’s worksheet, the teacher remind the basic concept of probability theory and its related topic. Related topics discuss are probability function, special distribution function, they are binomial and normal distribution. As assessment to the teacher, the devotee gave pretest in the first meeting and post test at the end of workshop. It item consist of lesson study concept, probability function, binomial and normal distribution. Depend on it, we see the increment of teacher’s competency.